2007
DOI: 10.2136/sssaj2006.0100
|View full text |Cite
|
Sign up to set email alerts
|

Soil Genesis and Mineral Transformation Across an Environmental Gradient on Andesitic Lahar

Abstract: Abbreviations: AL-7, alpine biome; Al d , citrate-dithionite-extractable aluminum; Al o , oxalate-extractable aluminum; Al p , pyrophospate-extractable aluminum; BO-1, blue oak biome; Fe d , citrate-dithionite extractable iron; Fe o , oxalate-extractable iron; PO-2, pine-oak biome; PP-3, ponderosa pine biome; RF-5, red fi r biome; SA-6, subalpine biome; Si o , oxalate-extractable silicon; SRO, short-range ordered; WF-4, white fi r biome; XRD, x-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 47 publications
7
70
2
1
Order By: Relevance
“…The extent of mass loss in topsoil layers due to vegetation fires is strongly correlated to SOM combustion (Rein et al, 2008). In all of our soils, statistically significant mass loss (p < 0.05) occurred within the temperature ranges of SOM combustion, between 250 to 450 • C. Proportion of soil mass loss with temperature was proportional to initial C concentration of the soils.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The extent of mass loss in topsoil layers due to vegetation fires is strongly correlated to SOM combustion (Rein et al, 2008). In all of our soils, statistically significant mass loss (p < 0.05) occurred within the temperature ranges of SOM combustion, between 250 to 450 • C. Proportion of soil mass loss with temperature was proportional to initial C concentration of the soils.…”
Section: Discussionmentioning
confidence: 60%
“…All the sites have a Mediterranean climate characterized by warm to hot dry summers and cool to cold wet winters. Mean annual air temperature ranges from 16.7 • C at the lowest site located at 210 m to 3.9 • C at the highest elevation site which is at an elevation of 2865 m. Annual precipitation ranges from 33 cm at the lowest site to 127 cm at the highest site Rasmussen et al, 2007) (Table 1).…”
Section: Study Site and Soil Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…to 3.9 • C at the highest elevation site at an elevation of 2865 m a.s.l. Annual precipitation ranges from 33 cm at the lowest site to 127 cm at the highest site (Dahlgren et al, 1997;Rasmussen et al, 2007) (Table 1).…”
Section: Study Site and Soil Descriptionmentioning
confidence: 99%
“…In landscapes where physical erosion is low, studies at multiple spatial scales have demonstrated that precipitation and temperature strongly control chemical weathering rates and soil development when all other state factors are held constant (Strakhov, 1967;Ruhe, 1984;Chadwick et al, 2003;Dahlgren et al, 1997;Rasmussen et al, 2007;Williams et al, 2010;Goodfellow et al, 2014). The degree of soil development varies considerably with changes in climate, with thresholds observed in weathering processes and soil formation between water-limited systems and energy-limited systems (Dahlgren et al, 1997;Rasmussen et al, 2011;Goodfellow et al, 2014).…”
mentioning
confidence: 99%